EGFR oligomerization organizes kinase-active dimers into competent signalling platforms - Sarah R. Needham (Nature Portfolio, 2016)
Epidermal growth factor receptors have been shown to oligomerise upon binding to their cognate ligands. Here, the authors use biochemical, biophysical and cell biology techniques to analyse the structures of these oligomers, and argue that these formations are required for signalling.